2005
DOI: 10.1523/jneurosci.0849-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

NMDA Receptor Activation Inhibits α-Secretase and Promotes Neuronal Amyloid-β Production

Abstract: Acute brain injuries have been identified as a risk factor for developing Alzheimer's disease (AD). Because glutamate plays a pivotal role in these pathologies, we studied the influence of glutamate receptor activation on amyloid-␤ (A␤) production in primary cultures of cortical neurons. We found that sublethal NMDA receptor activation increased the production and secretion of A␤. This effect was preceded by an increased expression of neuronal Kunitz protease inhibitory domain (KPI) containing amyloid-␤ precur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
127
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(134 citation statements)
references
References 61 publications
4
127
1
2
Order By: Relevance
“…Early studies showed that electrical depolarization increases the release of soluble APP-a in rat hippocampal brain slices (Nitsch et al 1993), and it appears that these effects are mediated by activation of muscarinic M1 acetylcholine receptors which leads to parallel decreases in Ab levels (Beach et al 2001;Hock et al 2003). On the other hand, specific stimulation of NMDA receptors up-regulates APP, inhibits a-secretase activity, and promotes Ab production (Lesne et al 2005).…”
Section: Activity-dependent App Processingmentioning
confidence: 99%
“…Early studies showed that electrical depolarization increases the release of soluble APP-a in rat hippocampal brain slices (Nitsch et al 1993), and it appears that these effects are mediated by activation of muscarinic M1 acetylcholine receptors which leads to parallel decreases in Ab levels (Beach et al 2001;Hock et al 2003). On the other hand, specific stimulation of NMDA receptors up-regulates APP, inhibits a-secretase activity, and promotes Ab production (Lesne et al 2005).…”
Section: Activity-dependent App Processingmentioning
confidence: 99%
“…Importantly, using antibodies against the N-terminal component of GluN1 or GluN2B subunits, our data supports that Aβ oligomers are able to bind NMDARs extracellularly (Costa et al, 2012). On the other hand, NMDARs activation (Lesne et al, 2005), and more particularly extrasynaptic activation (Bordji et al, 2010), triggers increased production and secretion of Aβ, which is preceded by a shift from APP695 to Kunitz protease inhibitory domain (KPI) containing APPs, isoforms exhibiting a high amyloidogenic potential, followed by a shift from α-secretase to β-secretase-mediated APP processing, largely suggesting a circuit in which Aβ facilitates NMDARs activation, which in turn promotes Aβ production.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Furthermore, NMDARs activation, particularly extrasynaptic NMDARs (Bordji et al, 2010), promote neuronal Aβ secretion (Lesne et al, 2005). Thus, the use of treatments targeting NMDARs seem to be a promising therapeutic option to counteract AD progression.…”
Section: Nmdars As Targets For Therapeutic Intervention In Admentioning
confidence: 99%
“…We initially demonstrated that a prolonged stimulation of cortical neuron cultures with a sublethal concentration of NMDA increased the production and secretion of A β (Lesn é et al, 2005 ). This effect was preceded by an important modifi cation of neuronal APP expression pattern with the expression of an APP isoform which is normally absent in neurons: the Kunitz protease inhibitor (KPI) domain containing APP (KPI-APP).…”
Section: Nmdar Activation and Neuronal A β Synthesismentioning
confidence: 99%
“…Moreover, excessive NMDAR activity was shown to contribute importantly to the etiology of many acute or chronic neurodegenerative disorders such as stroke, Hungtinton ' s disease, HIV-associated dementia and AD (Lipton and Rosenberg , 1994 ;Lancelot and Beal , 1998 ). Several studies reported a direct link between NMDAR overactivation on the one hand, and APP processing and neuronal A β secretion on the other hand, even if the conclusions could be somewhat different (Lesn é et al, 2005 ;Marcello et al , 2007 ;Hoey et al , 2009 ). It was further demonstrated that the cellular location of NMDARs is a key parameter controlling their effect on neuronal viability.…”
Section: Introductionmentioning
confidence: 99%